Factors determining the optimization of digital technology in rural schools - Omar, Muhd Khaizer; Dainal, Edward; Mohd Puad, Mohd Hazwan; Zakaria, Anis (Human Resource Management Academic Research Society, 2023)
Digital technology greatly benefits rural areas by providing access to information, education, and communication resources. For example, internet access can connect people in rural areas to online educational resources, job opportunities, and social networks. However, implementing digital technology in rural areas can be challenging due to myriad factors. In exploring the challenges and struggles of technology among students in rural areas, this research explores factors that contributed to the optimization of technology in rural localities. A quantitative descriptive and correlational study was employed on 231 fourth-grade secondary school students at the selected public schools in the eastern part of Malaysia. A set of questionnaires was developed and distributed on-field. Four variables were tested in this research: (a) knowledge, (b) motivation, (c) attitude, and (d) technology readiness. The findings demonstrated that knowledge of using digital technology was the prominent indicator depicting technology readiness among the studied population. Further discussions elaborated in this article promotes the better implementation of digital technology to rural school students which eventually prosper a meaningful learning ecosystem and embark nations’ strategic planning on digitization effort.